Pembangkitan dan Pemulihan Citra Biner Markov Random Field (MRF) secara Stokastik Dengan Algoritma Markov Chain Monte Carlo (MCMC) - Adi, Kusworo; Bayu Suksmono, Andrian (BERKALA FISIKA, 2009)
Ising model or the Spin Glass is a model used to solve the magnetic properties of materials and the occurrence of phase transitions from paramagnetic to ferromagnetic properties. Magnetization of the material comes from the vortex that has two kinds of electron spin, ie {-1 / 2, +1 / 2}. Both spin gives the direction of magnetization (North-South) that opposite. Two-dimensional Ising model (2D), often called a Markov Random Field (MRF). This model is a stochastic model that can represent the image texture. Result binary image generation MRF much affected by changes in temperature, the spin direction will be random if the environment inside a high enough temperature, ie above the critical tempertaur (or Currie temperature) Tc, at this kedaan paramagnetic material. Conversely, if the environmental temperature below Tc, then the material would be ferromagnetic. As for binary image restoration MRF is affected by noise levels and the number of iterations, the best results the image restoration process at the level of noise from 0 to 0.5. Â  Keywords: Â image restoration, markov random field, stochastic